Perceived Organizational Support and Affective Organizational Commitment: Does Employee’s Work-Life Balance Mediate the Relationship? - Saragih, Romat; Prasetio, Arif Partono; Luturlean, Bachruddin Saleh; Prasetio, Yahya Eka (International Journal of Psychosocial Rehabilitation, 2020)
The current study investigated whether perceived organizational support (POS) might be positively related to affective commitment to the organization. And whether work-life balance (WLB) mediated the relationship. The sample includes 315 participants working as an officer from various organizations in Indonesia. Results of regression analysis using SPSS 21 showed that organizational support has an additive effect on WLB and affective commitment. Furthermore, WLB also has a positive effect on affective commitment. The bootstrapping analysis also reveals there was no zero value in the lower and upper level, which mean WLB mediated the relationship of POS and affective commitment. These findings reinforce the importance of the presence of support from an organization in developing work-life balance and enhance employee affective commitment to the organization. An employee with affective commitment can help an organization to achieve its goals, thus organizations need to improve the level of support given to employees to increase WLB and affective commitment. Authors explain POS, WLB, and affective commitment using employees from various industries to explain workplace attitudes and behaviors in Indonesia.